Changes in soil and plant carbon pools after 9 years of experimental summer warming and increased snow depth - Hermesdorf, Lena; Mortensen, Louise H.; Blitz, Sophia B.; Jepsen, Malte S.; Westergaard-Nielsen, Andreas; Michelsen, Anders; Blok, Daan; Sigsgaard, Charlotte; Christiansen, Casper T.; Hansen, Birger Ulf; Elberling, Bo (The Science of the total environment, 2024)
Climate change can have positive and negative effects on the carbon pools and budgets in soil and plant fractions, but net effects are unclear and expected to vary widely within the arctic. We report responses after nine years (2012−2021) of increased snow depth (snow fences) and summer warming (open top chambers) and the combination on soil and plant carbon pools within a tundra ecosystem in West Greenland. Data included characteristics of depth-specific soil samples, including the rhizosphere soil, as well as vegetation responses of NDVI-derived traits, plant species cover and aboveground biomass, litter and roots. Furthermore, natural vegetation growth through the study period was quantified based on time-integrated NDVI Landsat 8 satellite imagery. Our results showed that summer warming resulted in a significant and positive vegetation response driven by the deciduous low shrub Betula nana (no other vascular plant species), while snow addition alone resulted in a significant negative response for Betula. A significant positive effect of summer warming was also observed for moss biomass, possibly driven increasing shade by Betula. The aboveground effects cascaded to belowground traits. The rhizosphere soil characteristics differed from those of the bulk soil regardless of treatment. Only the rhizosphere fraction showed responses to treatment, as soil organic C stock increased in near-surface and top 20 cm with summer warming. We observed no belowground effects from snow addition. The study highlights the plant species response to treatment followed by impacts on belowground C pools, mainly driven by dead fine roots via Betula nana. We conclude that the summer warming treatment and snow addition treatment separately showed opposing effects on ecosystem C pools, with lack of interactive effects between main factors in the combination treatment. Furthermore, changes in soil C are more clearly observed in the rhizosphere soil fraction, which should receive more attention in the future. [Display omitted] •9 years of summer warming and snow addition had contrasting effects on C pools.•Summer warming increased biomass, LAI and rhizosphere soil C.•Additional snow decreased biomass and NDVI, with no effect on soil C.•No interactive effect of snow addition and summer warming on biomass and soil C.•Betula nana was the key plant species, affecting biomass and organic C pools.